Applications of Coal Ash in the Production of Building Materials and Solving Environmental Problems - A.Kh. Alinazarov; M.A. Khusainov; A.H. Gaybullaev (Global Scientific Publishing, 2022)
The article discusses the technology of production of building materials using the ashes of thermal power plants. The methods of utilization of Angren brown coal ash as a filler of multicomponent cement materials, as well as the operating modes of the technology of production of products from ash-cement mixtures are shown. The results obtained show the high economic and environmental efficiency of the proposed technology in the production of building composite materials.
Keywords: ash; brown coal; ash utilization; structure formation